Embedding Aswaja Values in Strengthening Religious Moderation in Students - Latif, Abd; Ubaidillah; Mundir (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2023)
This study aims to examine empirically the variables in the inculcation of ASWAJA values (tawasuth, tawazun, tasamuh) in students of Madrasah Tsanawiyah Syirkah Salafiyah Pondok Pesantren Ad Dimyati Jenggawah Jember in an effort to strengthen religious moderation. It is hoped that the research will provide a scientific solution to reject and counteract the notions of radical and fanatical Islamic movements that seek to recruit young people, especially students, namely by instilling ASWAJA values in an effort to strengthen religious moderation. The research method used is descriptive qualitative. Data was collected through observation, documentation, and interview. Interviews were conducted with school principals, waka. Students, ASWAJA teachers and some student. The results showed that 1) the inculcation of ASWAJA values (tawasuth, tawazun, tasamuh) was manifested through ASWAJA learning in each class with meetings once a week and through the habituation of NU's amaliah activities in daily activities; 2) the inculcation of ASWAJA values is an indication of strengthening religious moderation in the community, especially in schools.